Real Time 5G Simulator - HRUSTIC, ADI (My University, 2022)
As we shift towards the introduction of 5G in the world, it is indisputable that tools for continuously testing such an environment are needed in order to ensure its success. Ericsson wants to become one of the leaders of 5G solutions with their Evolved Packet Gateway (EPG), which acts as a gateway between a radio network and the Internet. A core component of the EPG is the User Plane (UP), who is responsible for inspecting and transferring payload data of network packets, one of the processheaviest parts of the entire communication. To test the efficacy of the UP, Ericsson has several simulators at their disposal depending on the intended goal. Ericload is one such simulator that can send bidirectional data to the UP as a means to load test it. Currently, Ericload is able to generate model-based traffic, i.e., traffic calculated using mathematical models. While this approach is sensible, it does not entirely reflect the common properties found in real world traffic, such as self-similarity and long-range dependency. Trace-based modelling is a second approach of traffic generation, whose goal is to introduce the real world traffic properties into a simulation by replaying already captured network traces back to networks. The purpose of this thesis is to extend Ericload and implement scalable trace-based traffic modelling and load testing, as well analyze how this adage compares to model-based load testing. The analysis was done using metrics such as packet and data throughput, latency, as well as several verification approaches to ensure a correct trace-based simulation. The results conclude that the implementation of a basic trace-based traffic modelling was successful, and performs load tests well exclusively by itself or together with model-based traffic, without causing any severe performance issues. The results also shows, theoretically, how scaling captured traces affects its self-similar properties, and how to take these effects into consideration when making any further future improvements.
Keywords: packet capture; pcap; 5g; simulator; replay; trace-based; load testing